(untitled) (Journal of the College of Basic Education, 2026)
The research aimed to identify electronic isolation among middle school students, the significance of differences in electronic isolation according to the first stage variable, the second among middle school students, and to achieve the research objectives, the researcher built the electronic isolation scale, which consists of (29) paragraphs and each paragraph has trilogy alternatives, paragraphs have been confirmed by its psychomertric properties, as the scale was applied to a sample (100), a student who was chosen in a random class in a class to extract the results of the study, and the results of the research showed that the research sample members have the problem of electronic isolation, according to the hypothesis medium, there are no statistically significant differences in electronic isolation according to the stage of the stage (first, second), and in light of the results the researcher made a number of recommendations and proposals.